Wanprestasi Dalam Perjanjian Kredit Di Koperasi Wahana Makmur Kecamatan Ujung Batu Kabupaten Rokan Hulu - Dani, Suci Rahma; Bachtiar, Maryati; Putra, Setia (Jurnal Ilmiah Wahana Pendidikan, 2025)
Default is the non- fulfillment of the debtor’s obligations towards the creditor as previously agreed or in an agreement where one or both parties bound in an agreement do not carry out the obligations or achievements written in the agreement. According to article 1338 paragraph (1), the agreement made by the parties is law for those who make it. The credit agreement in the Wahana Makmur cooperative, Ujung Batu District, in which there was a default between the debtor and the creditor, in which the debtor did not make installment credit as previously promised by the cooperative due to the debtor’s declining economic situation and prioritizing other needs so that the installment credit was neglected. Defaults that occur result in losses for the Wahana Makmur cooperative. This research aims to determine the implementation and resolution of defaults between debtors and creditors in credit agreements at the Wahana Makmur cooperative, Ujung Batu District. The research method used is sociological or empirical research, namely interviews with the parties contained in the agreement as a data collection tool. In this research, the author conducted direct research at the research location to obtain data, materials and information related to this research. The conclusion that can be obtained from the results of this research is that regarding the implementation of the cooperative money loan credit agreement between the debinar party and the creditor which was agreed upon by the parties, it could not be implemented properly because the debtor was in default by not paying the credit installments. Settlement of defaults that occur in cooperative money loan credit agreements between debtors and creditors can be done by means of litigation and non-litigation, which is through litigation, namely through court and non-litigation or outside of court, namely through negotiation, communication, consultation mediation and expert opinions